Telomere lengthening and telomerase activation during human B cell differentiation - Weng, Nan-ping (National Academy of Sciences, 1997)
The function of the immune system is highly dependent on cellular differentiation and clonal expansion of antigen-specific lymphocytes. However, little is known about mechanisms that may have evolved to protect replicative potential in actively dividing lymphocytes during immune differentiation and response. Here we report an analysis of telomere length and telomerase expression, factors implicated in the regulation of cellular replicative lifespan, in human B cell subsets. In contrast to previous observations, in which telomere shortening and concomitant loss of replicative potential occur in the process of somatic cell differentiation and cell division, it was found that germinal center (GC) B cells, a compartment characterized by extensive clonal expansion and selection, had significantly longer telomeric restriction fragments than those of precursor naive B cells. Furthermore, it was found that telomerase, a telomere-synthesizing enzyme, is expressed at high levels in GC B cells (at least 128-fold higher than those of naive and memory B cells), correlating with the long telomeres in this subset of B cells. Finally, both naive and memory B cells were capable of up-regulating telomerase activity in vitro in response to activation signals through the B cell antigen receptor in the presence of CD40 engagement and/or interleukin 4. These observations suggest that a novel process of telomere lengthening, possibly mediated by telomerase, functions in actively dividing GC B lymphocytes and may play a critical role in humoral immune response by maintaining the replicative potential of GC and descendant memory B cells.